Impact of COVID-19 pandemic on the care of people with epilepsy and predictors of epilepsy worsening: Aswan/upper Egypt hospital-based study - Eman M. Khedr; Nourelhoda A. Haridy; Gellan K. Ahmed; Mohamed Nemr Othman; Abdelrahman S. Elsoghier; Bastawy M. Al Fawal (The Egyptian Journal of Neurology, Psychiatry and Neurosurgery, 2024)
Abstract Background During the Coronavirus disease pandemic “COVID-19”, epilepsy was one of many chronic neurological diseases in which treatment was neglected. This study aimed to evaluate the impact of the pandemic on people with epilepsy and identify potential predictors of seizure worsening through a face-to-face hospital survey. During the study period, 245 participants were recruited: 124 people with epilepsy (PwE) and 121 people without epilepsy (PwoE) age and sex-matched. Both groups were compared using sociodemographic COVID-19-related questionnaires and Hamilton Anxiety and Depression scales. PwE also completed epilepsy-specific questionnaires. Subsequently, we subdivided the PwE group into people with worsening epilepsy (WPwE) and those without (NWPwE). Results Compared with PwoE, PwE had significantly higher rates of COVID-19 infection (59.7% versus 41.3%, p = 0.004), and 69.4% of them (86/124) reported WPwE. WPwE had significantly higher rates of COVID-19 infection (75.6% versus. 23.7%, p < 0.0001), emergency room visits (69.8% versus 42.1%, p = 0.004), delayed neurology appointments (69.8% versus 42.1%, p = 0.004), and difficulties accessing medication (69.8% versus 47.4%, p = 0.02) and being less likely to be vaccinated (39.5% versus 68.4%, p = 0.003) than NWPwE. Depression and anxiety rates increased significantly during the pandemic compared with prior pandemics in both PwE and PwoE (p < 0.0001 for each). Moreover, the WPwE showed a significant increase in depression rates (33.7–60.5%, p < 0.0001) and higher mean anxiety scores compared to the NWPwE (p = 0.029). A multivariate binary logistic regression analysis showed that having a COVID-19 infection (AOR: 12.086, p < 0.0001), being laid off (AOR: 0.024, p = 0.001), or having more seizures before the pandemic (AOR: 3.366, p = 0.009) were all strong predictors of seizures getting worse. Conclusions Nearly 69% of PwE experienced pandemic-related seizures worsening, along with deterioration of mental health. Factors such as personal COVID-19 infection, unemployment, work interruption, and higher pre-COVID seizure frequency were identified as key predictors of seizure worsening. Mitigating these predictors could strengthen resilience among PwE during future widespread crises. Trial registration clinicaltrials.gov, NCT05205590. Registered on October 25, 2021—Retrospectively registered, https://classic.clinicaltrials.gov/ct2/show/NCT05205590